Hepatoprotective and Antioxidant Activities of Polyphenolic Extract of Pyrus communis Leaf in Carbon tetrachloride–Treated Albino Wistar Rats: Hepatoprotective effect of polyphenolic leaf extract of Pyrus communis - Didunyemi, Oluwafemi; Olasehinde, Oluwaseun (Journal of Tropical Life Science, 2024)
Polyphenols are active plant compounds that are reportedly capable of eliminating or limiting the deleterious side effects of free radicals and consequently restoring the functional integrity of important organs such as the liver. This study investigated the liver-protecting and antioxidant activities of PEP.c (Polyphenol leaf extract of Pyrus communis) against carbon tetrachloride-induced hepatotoxicity in wistar rats. Liver damage was induced via intraperitoneal (i.p.) injection of 1.5 mL/kg body weight (b.w.) of 50% carbon tetrachloride (CCl4) in olive oil on the 7th day of extract/drug administration. Induction of CCl4 significantly (P < 0.05) increased the activities of serum gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT) as well as a significant decrease (P < 0.05) in the serum level of total protein and the activity of superoxide dismutase and glutathione in the liver tissue with a concomitant increase in malondialdehyde (MDA) level. Oral administration of PEP.c (50, 100 and 250 mg/kg b.w.) for 7 days, significantly (P < 0.05) reduced the elevated serum levels of serum GGT, AST, ALT, ALP and increased the level of total protein as compared to CCl4-induced hepatotoxic-untreated group. However, administration of PEP.c significantly (P < 0.05) decreased concentration of malondialdehyde and increased the activity of the superoxide dismutase (SOD) as well as enhanced glutathione (GSH) level in the liver tissue. Results were compared to N-acetylcysteine, a known liver-protecting agent. Results from histopathological evaluation also supported the hepatoprotectivity of PEP.c in the CCl4- induced albino wistar rats. The results of this study suggested that PEP.c can be used as a safe and alternative drug for the prevention and management of liver injury.